A lysosome-targeting and polarity-specific fluorescent probe for cancer diagnosis. Issue 32 (3rd April 2019) - Fan, Li; Wang, Xiaodong; Ge, Jinyin; Li, Feng; Wang, Xiao; Wang, Juanjuan; Shuang, Shaomin; Dong, Chuan
Abstract : A lysosome-targeting and polarity-specific fluorescent probeCPM has been rationally designed for cancer diagnosis and imaging. Abstract : A lysosome-targeting and polarity-specific fluorescent probe CPM has been rationally designed for cancer diagnosis and imaging. We have successfully shown that lysosome polarity may serve as an ubiquitious marker for cancer detection. The potential of CPM for cancer diagnosis has also been demonstrated at the levels of live cells, organs, whole animal, and clinical patient tissue samples.